2007
DOI: 10.1007/s10865-007-9095-6
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Illness Severity, Self-Reported Cognitive Impairment, and Perceived Illness Management with Depression and Anxiety in a Multiple Sclerosis Clinic Population

Abstract: Within the multiple sclerosis (MS) population, high prevalence of psychiatric concerns, such as depression and anxiety, has been well documented. The purpose of this study was to examine factors contributing to higher depression and anxiety levels in a sample of 82 patients utilizing MS clinic services. Independent variables included MS physical severity, self-reported cognitive impairment, and perceived illness management, respectively. Results from hierarchical regression analyses indicated that depression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 53 publications
6
55
3
Order By: Relevance
“…12,14,15,22 In contrast, reports of cognitive concerns on the PDQ were highly correlated with concomitant reports of depression, anxiety, fatigue, and self-efficacy, in line with existing literature. 15,19,21 Among these variables, reports on the PDQ were most highly correlated with vegetative symptoms of depression (r = 0.60 to 0.66) addition, each index of the PDQ (ie, Attention, Memory, and Planning) maintained significant associations with each self-report factor. See Table 4 for the correlations with the specific breakdown of all the subscales of the PDQ.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…12,14,15,22 In contrast, reports of cognitive concerns on the PDQ were highly correlated with concomitant reports of depression, anxiety, fatigue, and self-efficacy, in line with existing literature. 15,19,21 Among these variables, reports on the PDQ were most highly correlated with vegetative symptoms of depression (r = 0.60 to 0.66) addition, each index of the PDQ (ie, Attention, Memory, and Planning) maintained significant associations with each self-report factor. See Table 4 for the correlations with the specific breakdown of all the subscales of the PDQ.…”
Section: Resultsmentioning
confidence: 95%
“…They suggested that further attention to the role of self-efficacy was warranted as both a direct and mediating effect on perceived functioning. 21 The aim of the present study was, thus, to examine the relationship between subjective cognitive concerns on the PDQ and objective neuropsychological performance while taking into account the possible confounding factors of depression, anxiety, fatigue, and selfefficacy. We hypothesized that the correlation between subjective cognitive concerns and objective performance on a neuropsychological test battery would be inconsistent, at best.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that depression in patients with MS is related to a poorer quality of life, diminished positive outlook, and, most importantly, reduced adherence to treatment. [24][25][26][27] Therefore, a history of depression has led to many prescribers avoiding IFNβ therapy for their patients, based on findings in the pivotal interferon studies that suggested a possible increase in depressive symptoms after starting IFNβ therapy. 1,11 This study as well as other comparison studies have not supported those earlier findings.…”
Section: Use Of Concomitant Antidepressant Medicationmentioning
confidence: 99%
“…However, the prevalence of anxiety and its relation to socio-demographic and clinical characteristics of the MS patient population is much less thoroughly investigated than prevalence of depression in the general population and needs much more attention from scientists [19].…”
Section: Discussionmentioning
confidence: 99%